Factors Affecting Students’ Satisfaction with a Course: Does Physical Environment Matters? - Batouei, Amir; Teoh, Ai Ping (Journal of Entrepreneurship, Business and Economics; Vol 9 No 2 (2021), 2021)
This study intends to examine factors that influence students’ satisfaction with a course and how this satisfaction with a course affects course recommendation. Furthermore, the moderating effects of the physical classroom environment were examined in the relationship between the factors and students’ satisfaction with a course. Data were collected from students in private universities in Kuala Lumpur, Malaysia and was analyzed using Partial Least Squared Method (PLS). The results showed that course evaluation, instructional support, students self-efficacy all have a significant positive effect on students’ satisfaction with a course, and students’ satisfaction with a course positively influences course recommendation. However, our results did not find a significant relationship between the student-teacher relationship and students’ satisfaction with a course. Moreover, our findings confirmed the moderating role of the physical classroom environment on the relationship between course evaluation, instructional support, students’ self-efficacy, student-teacher relationship and course satisfaction. Research paper Keywords: Course Evaluation; Instructional Support; Self-Efficacy; Physical Classroom Environment; Student Satisfaction; Course Recommendation; Higher Education; Malaysia Reference to this paper should be made as follows: Batouei, A., & Teoh, A. P. (2021). Factors Affecting Students’ Satisfaction with a Course: Does Physical Environment Matters?. Journal of Entrepreneurship, Business and Economics , 9 (2), 132–173.